Estudo dos sistemas de produção dos agricultores familiares da fronteira oeste do Rio Grande do Sul - Alende, Carlos Roberto Maciel (2006)
In Brazil, the historical negligence with the familiar agriculture deepen itself through the persistence of the traditional development paradigm, boosted by the campo conservative modernization which has privileged the rural latifundia patronage class, mostly through the rural credit public politic and the technical assistance. Beyond that, in the Brazilian rural environment the familiar class has resisted maintaining their production units along important development for the national economy. In 2006, as a rural development and supporting strategy axis the Brazilian government has approved the Familiar Agriculture Law in order to improve the familiar agriculture. In this way, the political priorities assuming the familiar agriculture in Brazil justified the studies accomplishment to understand the particularities and to build objective and factual formulations for the development of the economically disfavored regions considered belated in the country. In the State of Rio Grande do Sul, the socioeconomic development shows acute differences between North and South of the State. The prevalent ethnical groups spacialization, the implemented production matrixes and the agro ecological conditions, beyond others indicators, when analyzed, flash themselves in the social and economical differences of these regions, mainly on the development stagnation of the South of the State. The South West Border is identified as a region constituted, on the agrarian approach, only by large rural properties, formed from land distribution which breed farms / farmers. The region is referred as a place of traditional latifundia, extensive cattleraising production. These establishments practice, mostly, beef cattle raising and/or ovine, familiar labor-force predominance, however, there are also horticulture and dairy cattle establishments. This essay has substantiated, with relevance on the familiar agriculturists production systems for the development of the studied region, the diversity of both natural factors as human elements which dominate the complex dynamic of the West Border agrarian spaciality.The methodological procedures basing on Diagnostics Analysis of the Agrarian Systems enable to characterize the production systems of the familiar agriculturists, their potentialities and bounds adopting the municipal district of Alegrete as a reference. This study has confirmed that the social heterogeneity of the familiar process on the region is made up of different types of familiar agriculturists.